2022
DOI: 10.3390/molecules27249052
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Common Cooking and Drying Methods on Phytochemical and Antioxidant Properties of Corchorus olitorius Identified Using Liquid Chromatography-Mass Spectrometry (LC-MS)

Abstract: In this study, Corchorus olitorius leaves were subjected to different thermal treatments (blanching, boiling, drying, frying, and steaming) and analyzed for proximate composition, total phenolic content (TPC), total flavonoid content (TFC), and antioxidant activity. Furthermore, Fourier transform infrared spectroscopy (FTIR) was used to identify functional groups, while metabolites were identified with LC-MC. The TPC and antioxidant activity of C. olitorius were significantly (p < 0.05) increased by cooking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
(72 reference statements)
1
1
0
Order By: Relevance
“…However, a considerable increase in the total content of phenolic acids was observed in certain pretreated samples, specifically S10—F and B6—F, which had been subjected to steaming and blanching. Similar results were reported by Ncube, who observed a significant increase in the content of phenolic acids such as chlorogenic acid and crypto-chlorogenic acid in blanched Corchorus olitorius ( Ncube, Dlamini, & Beswa, 2022 ). According to Feumba Dibanda, phenolic acids with conjugated structures, such as ferulic acid and p -coumaric acid, which are found in fruits and vegetables, may be present in esterified forms ( Feumba Dibanda, Panyoo Akdowa, Rani, Metsatedem Tongwa, & Mbofung, 2020 ).…”
Section: Discussionsupporting
confidence: 89%
“…However, a considerable increase in the total content of phenolic acids was observed in certain pretreated samples, specifically S10—F and B6—F, which had been subjected to steaming and blanching. Similar results were reported by Ncube, who observed a significant increase in the content of phenolic acids such as chlorogenic acid and crypto-chlorogenic acid in blanched Corchorus olitorius ( Ncube, Dlamini, & Beswa, 2022 ). According to Feumba Dibanda, phenolic acids with conjugated structures, such as ferulic acid and p -coumaric acid, which are found in fruits and vegetables, may be present in esterified forms ( Feumba Dibanda, Panyoo Akdowa, Rani, Metsatedem Tongwa, & Mbofung, 2020 ).…”
Section: Discussionsupporting
confidence: 89%
“…This study con rmed the changes in total phenolic content of Bletilla striata scented tea following different drying treatments [16] . However, Ncube Buyile and colleagues [17] showed that the total phenolic content of Corchorus olitorius leaves was increased by cooking. The difference may be related to the phenolic species.…”
Section: The Contents Of Eight Functional Componentsmentioning
confidence: 99%